Stability of the high-current ion beam compensated by electron beam in the induction LINAC drift gap filled with the dense electron cloud - Karas, V.I.; Kornilov, Ye.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V.; Silkin, M.Yu. (Вопросы атомной науки и техники, 2013)
In the work an injection of high-current electron and ion beams in a drift gap of the linear induction accelerator with collective focusing is studied. Consideration is carried out by means of numerical simulation by PIC-method in frame of full Vlasov-Maxwell equations set. It is shown, that a filling of a drift gap with the dense electron cloud, which is confined by magnetic field of trap configuration, on the one hand, provides charge compensation. However, on the other hand, it promotes development of electron and ion beams instability. Parameters (cloud density and temperature) and conditions, at which the energy spread of pulsed high-current (the density of particles 7·10¹⁷ m⁻³) ion beam does not exceed several percent are chosen. Розглядається інжекція потужнострумових електронного та іонного пучків у дрейфовий проміжок лінійного індукційного прискорювача з колективним фокусуванням. Розгляд проводиться за допомогою числового моделювання методом макрочастинок у рамках повної системи рівнянь Власова-Максвелла. Показано, що заповнення дрейфового проміжку щільною електронною хмарою, яка утримується магнітним полем пасткової конфігурації, з одного боку, забезпечує зарядову компенсацію, але, з іншого боку, сприяє розвитку нестійкості електронного і іонного пучків. Обрані параметри (густина і температура хмари) та умови, за яких розкид за енергією імпульсного потужнострумового іонного пучка (густина частинок 7·10¹⁷ m⁻³) не перевищує декількох відсотків. Рассматривается инжекция сильноточных электронного и ионного пучков в дрейфовый промежуток линейного индукционного ускорителя с коллективной фокусировкой. Рассмотрение проводится с помощью численного моделирования методом макрочастиц в рамках полной системы уравнений Власова-Максвелла. Показано, что заполнение дрейфового промежутка плотным электронным облаком, удерживаемым магнитным полем ловушечной конфигурации, с одной стороны, обеспечивает зарядовую компенсацию, но, с другой стороны, способствует развитию неустойчивости электронного и ионного пучков. Выбраны параметры (плотность и температура облака) и условия, при которых разброс по энергии импульсного сильноточного ионного пучка (плотность частиц 7·10¹⁷ m⁻³) не превышает нескольких процентов.